A gas adsorbent for high-purity gas production and a method for preparing the same

CN122032480BActive Publication Date: 2026-10-30DALIAN HUABANG CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610482223.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-13
Publication Date
2026-10-30
Estimated Expiration
2046-04-13

AI Technical Summary

Technical Problem

[0006]发明目的:针对现有高纯气体净化材料普遍存在的脱氧效率与多杂质协同去除能力难以兼顾、结构稳定性不足、传质阻力大、再生性能差以及在高温复杂气氛中易失活等问题,本发明提供一种高纯度气体生产的气体吸附剂及其制备方法,以克服上述问题

Benefits of technology

(1)构建短扩散路径与多尺度孔道,提高氧、水、二氧化碳及VOCs在材料内部的传质效率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a gas adsorbent for high-purity gas production and a preparation method thereof. The gas adsorbent comprises a hollow porous alumina inner layer, a CeO2-ZrO2 composite oxide intermediate layer and a Ni-Ce-Y composite active outer layer in sequence, forms a three-layer structure and constructs a hierarchical pore channel system with macro-pores, mesopores and micropores. The material is prepared by constructing a hollow alumina framework through a carbon sphere template method, forming a CeO2-ZrO2 intermediate layer through a uniform deposition method and then loading a Ni-Ce-Y active component through impregnation-calcination. The obtained adsorbent has excellent mass transfer performance and a synergistic purification function, can simultaneously and efficiently remove impurities such as hydrogen, oxygen, carbon monoxide, carbon dioxide and moisture in inert gas at room temperature, can stably reduce the outlet impurity concentration to the ppb level and can still maintain a high purification depth and adsorption capacity after multiple adsorption-regeneration cycles. The gas adsorbent has stable structure and strong applicability and is suitable for high-purity inert gas refining in the fields of electronic grade, energy and high-end manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gas purification technology, and in particular to a gas adsorbent for producing high-purity gas and its preparation method. Background Technology

[0002] High-purity gases (such as high-purity nitrogen, argon, helium, and other inert gases) are widely used in semiconductor manufacturing, flat panel displays, lithium batteries, photovoltaic materials, fine chemicals, and high-end metal smelting. These applications have extremely stringent requirements for the content of impurities such as oxygen, water, carbon dioxide, and trace volatile organic compounds (VOCs) in the gases, typically needing to be controlled at the ppm or even ppb level. Improper impurity control can easily lead to problems such as metal oxidation, electrode failure, device performance degradation, and decreased product yield. Therefore, developing gas adsorption / purification materials that combine efficient deoxygenation with synergistic removal of multiple impurities is an important technological direction in the field of high-purity gas preparation and deep purification.

[0003] Existing industrial gas purification systems mainly fall into two categories: physical adsorption materials and chemical reaction-based purifiers. Physical adsorption materials, such as activated alumina, molecular sieves, activated carbon, and porous silica gel, primarily rely on their pore structure and surface polarity to adsorb water, carbon dioxide, and VOCs. However, their oxygen removal capacity is limited, and they suffer from insufficient stability under high temperature, high humidity, or complex atmospheric conditions, easily leading to adsorption saturation and structural degradation. Chemical deoxidizers, such as copper-based, nickel-based, or noble metal-based catalysts / reactants, can achieve efficient deoxygenation through redox reactions, but they generally suffer from limited effective interaction interfaces, easy sintering and deactivation of the metal active phase, insufficient thermal stability, and poor tolerance to water and organic impurities, making it difficult to simultaneously meet the needs of synergistic purification of multiple impurities.

[0004] In recent years, composite metal oxides and core-shell structured materials have been increasingly applied in the field of gas purification. However, most existing technologies are still limited to single-function designs, with simple structural hierarchies, long mass transfer pathways, and low utilization rates of active sites. Furthermore, the materials are mostly solid particles or simply coated structures, which are prone to stress concentration and pore structure collapse during thermal cycling and regeneration, leading to adsorption capacity decay and shortened service life. In addition, for complex conditions where inert gases simultaneously contain oxygen, water, carbon dioxide, and trace VOCs, there is still a lack of multifunctional gas adsorbents that combine high deoxygenation efficiency, synergistic removal of multiple pollutants, and long-term thermal stability.

[0005] Therefore, there is an urgent need to develop a novel composite gas adsorbent with a hollow buffer space and hierarchical porous mass transfer channels in its structure, and with both oxygen storage oxides and highly active transition metal sites in its composition. Through multi-level structure and multi-component synergy, it can achieve efficient deoxygenation, deep purification and excellent regenerability to meet the urgent needs of high-purity gas production for high efficiency, long life and adaptability to complex impurities. Summary of the Invention

[0006] Purpose of the invention: To address the common problems of existing high-purity gas purification materials, such as difficulty in simultaneously achieving deoxygenation efficiency and multi-impurity synergistic removal capabilities, insufficient structural stability, high mass transfer resistance, poor regeneration performance, and easy deactivation in high-temperature and complex atmospheres, this invention provides a gas adsorbent for high-purity gas production and its preparation method to overcome the above-mentioned problems.

[0007] The technical solution of this invention: In a first aspect, the present invention provides a gas adsorbent for producing high-purity gas, the gas adsorbent having a three-layer structure, the three-layer structure comprising an inner layer, a middle layer and an outer layer; the inner layer material is a porous alumina framework; the middle layer material is a CeO2-ZrO2 composite oxide; and the outer layer material is a Ni-Ce-Y composite active phase.

[0008] In some embodiments, the porous alumina framework is a hollow structure. A suitable hollow volume fraction can balance heat transfer efficiency and mechanical strength.

[0009] In some embodiments, the molar ratio of Ce to Zr in the CeO2-ZrO2 composite oxide is 4:6 to 7:3.

[0010] In some embodiments, the molar ratio of Ni, Ce, and Y in the Ni-Ce-Y composite active phase is 5~10:2~4:1.

[0011] The loading amount of the outer composite active phase in the adsorbent is 3~15wt%.

[0012] In a second aspect, the present invention provides a method for preparing the gas adsorbent, specifically comprising the following steps: S1: Add glucose to deionized water and heat to carry out hydrothermal reaction to obtain carbon ball template; mix carbon ball template with aluminum source and solvent, add complexing agent, heat and stir, then add water / ethanol mixture, continue stirring, let stand for aging, filter, dry and calcin to obtain hollow porous alumina skeleton material. S2: Weigh out Ce source and Zr source, mix them and dissolve them in solvent to obtain metal ion solution, add hollow porous alumina framework material, and heat the reaction in a water bath; after the reaction is completed, filter, wash, dry and calcine to obtain hollow Al2O3@CeO2-ZrO2 composite oxide support; S3: Dissolve Ni salt, Ce salt, and Y salt in deionized water to prepare an impregnation solution; add hollow Al2O3@CeO2-ZrO2 composite oxide carrier to the impregnation solution, impregnate in a drum, let stand, heat to dry and calcine to obtain the gas adsorbent.

[0013] In some embodiments, the ratio of glucose to deionized water added is 3-4g:30-50ml; the hydrothermal reaction temperature is 160-200℃, and the reaction time is 4-10h.

[0014] In some embodiments, the aluminum source is aluminum isopropoxide; the ratio of the carbon ball template to the aluminum source is 10~30g:0.3~0.8mol; and the complexing agent is glacial acetic acid.

[0015] In some embodiments, the drying temperature in S1 is 50~80℃ and the drying time is 6~12h; the calcination atmosphere is air atmosphere, the calcination temperature is 400~500℃ and the calcination time is 3~4h.

[0016] In some embodiments, the Ce source can be Ce(NO3)3·6H2O, and the Zr source can be ZrO(NO3)2·H2O, but is not limited to the above selections.

[0017] In some embodiments, the ratio of the total metal ion concentration of the Ce source and Zr source to the added concentration of the hollow porous alumina framework material is 0.05~0.2 mol / L: 20~80 g / L. By controlling the total amount of Ce and Zr precursors added, the loading of CeO2~ZrO2 on the hollow alumina framework is 15~30 wt%.

[0018] If the precursor concentration is too low, the loading capacity will be insufficient, the functional layer will be discontinuous, resulting in insufficient oxygen storage capacity and weak stability and buffering effect on Ni. If the precursor concentration is too high, it will rapidly and spontaneously nucleate in the solution, reducing the proportion that is actually loaded onto the carrier and wasting raw materials. Alternatively, it may form a shell on the outer surface, causing the hollow structure to be "sealed" and the mesopores / macropores to be blocked, resulting in a significant decrease in specific surface area and pore volume.

[0019] In some embodiments, the heating temperature of the water bath heating reaction in S2 is 80~100℃, and the reaction time is 2~6h; the drying temperature of the calcination after drying in S2 is 80~120℃, and the drying time is 6~12h; the calcination temperature is 450~600℃, and the calcination time is 2~5h.

[0020] In some embodiments, the Ni salt can be Ni(NO3)2·6H2O, the Ce salt can be Ce(NO3)3·6H2O, and the Y salt can be Y(NO3)3·6H2O, but the choice is not limited to the above.

[0021] In some embodiments, the volume ratio of the impregnation liquid to the hollow Al2O3@CeO2-ZrO2 composite oxide carrier is 0.9~1.1:1; the impregnation temperature of the drum is 20~40℃, the impregnation time is 20~60min, and the standing time is 1~4h.

[0022] In some embodiments, the drying temperature for heating, drying and calcining in step S3 is 60~100℃, and the drying time is 6~10h; the calcination step is to first keep warm at 300~400℃ for 0.5~2h, and then calcinate at 450~650℃ for 2~5h.

[0023] Furthermore, the preparation method also includes molding, the molding step of which includes mixing the obtained gas adsorbent with a binder, adding deionized water to knead, extruding into columnar particles, and heating and calcining to obtain the molded adsorbent.

[0024] In some embodiments, the binder is pseudocrystalline boehmite, and the amount of binder added is 2 to 6 wt% of the forming adsorbent.

[0025] Beneficial effects: (1) Construct short diffusion paths and multi-scale channels to improve the mass transfer efficiency of oxygen, water, carbon dioxide and VOCs inside the material; (2) The reversible oxygen storage and release characteristics of CeO2-ZrO2 composite oxides are utilized to improve the deoxidation capacity and dynamic stability of the system; the supported composite active phase provides efficient deoxidation and organic impurity conversion sites, and the two form an obvious interface synergistic effect, so that the material can still maintain stable and efficient deoxidation capacity under low oxygen partial pressure conditions. (3) The hierarchical porous oxide framework has good physical adsorption capacity for moisture, carbon dioxide and some VOCs, while the transition metal / oxygen storage oxide system can chemically remove oxygen and some oxidizable organic impurities, thereby achieving simultaneous purification of multiple impurities by a single material and reducing the system complexity brought about by traditional multi-stage purification devices.

[0026] (4) The hollow structure effectively alleviates thermal stress concentration. The CeO2-ZrO2 composite oxide shell can inhibit metal particle migration and sintering, significantly improving the structural stability of the material during high temperature and multiple regeneration processes. It can still maintain a high specific surface area and activity level after oxidation-reduction cycle, making it suitable for continuous industrial operation and multi-cycle regeneration. Detailed Implementation

[0027] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.

[0028] Unless otherwise specified, all chemical reagents used in this invention are commercially available analytical grade reagents.

[0029] Example 1 S1: Add 40g of glucose to 400mL of deionized water, stir to dissolve, transfer to a reaction vessel, heat at 180℃ for hydrothermal reaction for 6h, cool to room temperature after reaction, centrifuge and wash, dry at 60℃ to obtain carbon sphere template; mix 20g of carbon sphere template with 0.5mol aluminum isopropoxide and 500mL of anhydrous ethanol, add 5mL of glacial acetic acid as a complexing agent, stir at 60℃ for 30min, then dropwise add 400mL of water / ethanol (volume ratio 1:4), continue stirring for 1h, let stand for aging for 2h, filter, dry at 80℃ for 12h, and then calcine at 450℃ for 4h in air atmosphere to obtain hollow porous alumina framework material; S2: Weigh 0.04 mol Ce(NO3)3·6H2O and 0.06 mol ZrO(NO3)2·H2O, mix and dissolve in 1000 mL deionized water, add 0.30 mol urea, and stir until completely dissolved; add 50 g of hollow porous alumina framework material, heat in a water bath at 90℃ for 4 h; after the reaction, filter and wash until pH=7, dry at 100℃ for 10 h, and then calcine at 500℃ for 3 h in air atmosphere to obtain hollow Al2O3@CeO2-ZrO2 composite oxide support; S3: Dissolve 0.08 mol Ni(NO3)2·6H2O, 0.02 mol Ce(NO3)3·6H2O, and 0.005 mol Y(NO3)3·6H2O in 1000 mL of deionized water to prepare an impregnation solution; add the hollow Al2O3@CeO2-ZrO2 composite oxide carrier to the impregnation solution, impregnate in a drum at 30°C for 30 min, let stand for 2 h, then dry at 80°C for 8 h, and then pre-calcine at 350°C for 1 h and calcine at 550°C for 3 h in air atmosphere to obtain the gas adsorbent.

[0030] Comparative Example 1 The preparation steps of the gas adsorbent provided in Comparative Example 1 are basically the same as those in Example 1, with the only difference being: In step 2, the molar amounts of Ce(NO3)3·6H2O and ZrO(NO3)2·H2O added are 0.1 mol and 0 mol, respectively.

[0031] Comparative Example 2 The preparation steps of the gas adsorbent provided in Comparative Example 2 are basically the same as those in Example 1, with the only difference being: In step 2, the molar amounts of Ce(NO3)3·6H2O and ZrO(NO3)2·H2O added are 0 mol and 0.1 mol, respectively.

[0032] Comparative Example 3 The preparation steps of the gas adsorbent provided in Comparative Example 3 are basically the same as those in Example 1, with the only difference being: In step 3, the molar amounts of Ni(NO3)2·6H2O, Ce(NO3)3·6H2O, and Y(NO3)3·6H2O added are 0.08 mol, 0.03 mol, and 0 mol, respectively.

[0033] Comparative Example 4 The preparation steps of the gas adsorbent provided in Comparative Example 4 are basically the same as those in Example 1, with the only difference being: In step 3, the molar amounts of Ni(NO3)2·6H2O, Ce(NO3)3·6H2O, and Y(NO3)3·6H2O added are 0.08 mol, 0.02 mol, and 0 mol, respectively, and an additional 0.005 mol of Cu(NO3)2 is added.

[0034] Comparative Example 5 The preparation steps of the gas adsorbent provided in Comparative Example 5 are basically the same as those in Example 1, with the only difference being: In step 2, the molar amounts of Ce(NO3)3·6H2O and ZrO(NO3)2·H2O added are 0.12 mol and 0.18 mol, respectively.

[0035] Comparative Example 6 S1: Weigh 100g Al(NO3)3·9H2O and dissolve it in 800mL of deionized water. Stir to form a clear solution. Under room temperature conditions, add 25% ammonia water dropwise with vigorous stirring to adjust the pH of the solution to 9, generating a white aluminum hydroxide precipitate. Continue stirring for 1 hour, then filter, wash with deionized water until pH=7, dry at 100℃ for 12 hours, and then calcine at 500℃ for 4 hours in air atmosphere to obtain solid porous alumina powder. S2: Weigh 4 mol Ce(NO3)3·6H2O and 6 mol ZrO(NO3)2·H2O, mix and dissolve in 1000 mL deionized water, add 50 g solid porous alumina powder, and impregnate for 1 h under a water bath at 30℃; after standing for 2 hours, take it out, dry at 100℃ for 8 h, and then calcine at 500℃ for 3 h in air atmosphere to obtain hollow Al2O3@CeO2-ZrO2 composite carrier; S2: Dissolve 0.08 mol Ni(NO3)2·6H2O, 0.02 mol Ce(NO3)3·6H2O, and 0.005 mol Y(NO3)3·6H2O in 1000 mL of deionized water to prepare an impregnation solution; add the hollow Al2O3@CeO2-ZrO2 composite carrier to the impregnation solution, impregnate in a drum at 30°C for 30 min, let stand for 2 h, then dry at 80°C for 8 h, and then pre-calcine at 350°C for 1 h and calcine at 550°C for 3 h in air atmosphere to obtain the gas adsorbent.

[0036] The gas adsorbent prepared above was mixed with 5 wt% pseudocrystalline boehmite, kneaded with deionized water, and extruded into columnar particles with a diameter of 5 mm. After drying at 110 °C for 6 h and calcining at 550 °C for 2 h, the shaped adsorbent was obtained.

[0037] The following tests were performed on the molded adsorbent: Activation of the formed adsorbent: Take 25 ml of catalyst sample, sieved to 20-40 mesh, and place it into a 1-inch stainless steel reaction tube. First, purge the pipeline and reaction tube with high-purity nitrogen at room temperature and pressure. After the entire evaluation system is free of oxygen, raise the temperature to 400℃ and run the gas at a space velocity of 5000 h⁻¹. -1 The catalyst is activated by introducing N2 containing 2-10% H2. After 4 hours of activation, the catalyst is purged with high-purity nitrogen to cool down to room temperature, thus completing the catalyst activation.

[0038] Preparation of raw material gas: According to the experimental requirements, the raw material gas with different impurity concentrations is prepared. The raw material gas base gas is high-purity nitrogen gas, which contains impurities of 100ppm hydrogen, 100ppm oxygen, 100ppm carbon monoxide, 100ppm carbon dioxide, 50ppm methane, and 10ppm water.

[0039] Experimental procedure: At room temperature (25℃) and pressure (0-20 kPa), space velocity was 10000 h⁻¹ -1 The prepared feed gas was introduced. During the evaluation process, the impurity content of the gas at the reactor outlet was monitored online to obtain the purification depth data of the molded adsorbent for different gases. When the content of a certain impurity in the outlet gas exceeded 10 ppb, the molded adsorbent was considered to be saturated for that impurity, and its adsorption capacity was calculated. The experimental results are shown in Table 1.

[0040] Activation and regeneration: To evaluate regeneration performance, after the formed adsorbent becomes saturated with adsorption of various impurities during the experiment, the feed gas is shut off, and high-purity nitrogen is switched to purge the catalyst layers for at least 6 hours. Then, the temperature is raised to 250℃ under normal pressure, and the catalyst is purged at a space velocity of 100–500 h⁻¹. -1 High-purity hydrogen is introduced for reduction. After 4 to 12 hours of reduction, the temperature is lowered, and then high-purity nitrogen is introduced to replace the bed to complete the activation and regeneration.

[0041] Experimental procedure: At room temperature (25℃) and pressure (0-20 kPa), space velocity was 10000 h⁻¹ -1 The prepared feed gas was introduced. During the evaluation process, the impurity content of the gas at the reactor outlet was monitored online to obtain the purification depth data of the molded adsorbent for different gases. When the content of a certain impurity in the outlet gas exceeded 10 ppb, the molded adsorbent was considered saturated for that impurity, and its adsorption capacity was calculated. After adsorption saturation, the molded adsorbent was regenerated according to the activation and regeneration steps, and then the experimental process was repeated for evaluation. The experimental results are shown in Tables 2 and 3.

[0042] Table 1 Experimental Results

[0043] Note: S1 in the table represents Example 1; D1 to D7 in the table represent Comparative Examples 1 to 7, respectively.

[0044] Table 2 Results of the regeneration experiment of the gas adsorbent in Example 1

[0045] Table 2. Results of the regeneration experiment of the gas adsorbent in Comparative Example 6

[0046] The data in the table show that, in Comparative Example 1, the intermediate layer only contains Ce, reducing the system from a "high-efficiency oxygen supply type" to a "common oxygen storage type," significantly weakening its deoxygenation, CO removal, and hydrogen removal capabilities, especially hindering stable output at the ppb level. In Comparative Example 2, the Ce-free intermediate layer almost completely eliminates the material's "refining" gas purification capabilities, limiting its use to ordinary desiccants and weak deoxidizers, failing to meet high-purity gas requirements. In the outer active phase, the absence of Y element results in short-term usability but significant long-term degradation, particularly in systems containing water or CO2, leading to rapid performance decline and reduced lifespan. Replacing Y element in the outer layer with Cu increases the adsorbent's affinity for CO but reduces the system's synergistic ability with multiple impurities, hindering long-term inert gas purification.

[0047] Compared with non-hierarchical three-layer structure materials, the hollow hierarchical porous three-layer structure prepared in this invention can still maintain ppb-level purification capacity after multiple adsorption-regeneration cycles. After 50 cycles, the capacity retention rate of each impurity is still as high as 80%. In contrast, the comparative material shows obvious premature penetration and loss of ppb capacity after 10 cycles, and the capacity decays by more than 50% after 50 cycles, which is difficult to meet the requirements of high-purity inert gas purification.

[0048] The present invention can also be implemented in various other ways. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the appended claims.

Claims

1. A gas adsorbent for producing high-purity gas, characterized in that, The gas adsorbent has a three-layer structure, which includes an inner layer, a middle layer, and an outer layer. The inner layer material is a porous alumina framework, wherein the porous alumina framework is a hollow structure; The middle layer material is a CeO2-ZrO2 composite oxide, wherein the molar ratio of Ce to Zr in the CeO2-ZrO2 composite oxide is 4:6~7:3; The outer layer material is a Ni-Ce-Y composite active phase, wherein the molar ratio of Ni, Ce, and Y in the Ni-Ce-Y composite active phase is 5~10:2~4:

1.

2. The method for preparing the gas adsorbent according to claim 1, characterized in that, Includes the following steps: S1: Add glucose to deionized water and heat to carry out hydrothermal reaction to obtain carbon ball template; mix carbon ball template with aluminum source and solvent, add complexing agent, heat and stir, then add water / ethanol mixture, continue stirring, let stand for aging, filter, dry and calcin to obtain hollow porous alumina skeleton material. S2: Weigh out Ce source and Zr source, mix them and dissolve them in solvent to obtain metal ion solution, add hollow porous alumina framework material, and heat the reaction in a water bath; after the reaction is completed, filter, wash, dry and calcine to obtain hollow Al2O3@CeO2-ZrO2 composite oxide support; S3: Dissolve Ni salt, Ce salt, and Y salt in deionized water to prepare an impregnation solution; add hollow Al2O3@CeO2-ZrO2 composite oxide carrier to the impregnation solution, impregnate in a drum, let stand, heat to dry and calcine to obtain the gas adsorbent.

3. The method for preparing the gas adsorbent according to claim 2, characterized in that, The ratio of glucose to deionized water added is 3~4g:30~50ml; the hydrothermal reaction temperature is 160~200℃, and the reaction time is 4~10h.

4. The method for preparing the gas adsorbent according to claim 2, characterized in that, The aluminum source is aluminum isopropoxide; the ratio of the carbon ball template to the aluminum source is 10~30g:0.3~0.8mol; the complexing agent is glacial acetic acid; the drying temperature in S1 is 50~80℃, and the drying time is 6~12h; the calcination atmosphere is air, the calcination temperature is 400~500℃, and the calcination time is 3~4h.

5. The method for preparing the gas adsorbent according to claim 2, characterized in that, The ratio of the total metal ion concentration of the Ce source and Zr source to the added concentration of the hollow porous alumina framework material is 0.05~0.2 mol / L: 20~80 g / L.

6. The method for preparing the gas adsorbent according to claim 2, characterized in that, The volume ratio of the impregnation solution to the hollow Al2O3@CeO2-ZrO2 composite oxide carrier is 0.9~1.1:1; the impregnation temperature of the drum is 20~40℃, the impregnation time is 20~60min, and the standing time is 1~4h.

7. The method for preparing the gas adsorbent according to claim 2, characterized in that, The drying temperature for heating, drying and calcining described in S3 is 60~100℃, and the drying time is 6~10h; the calcination step is to first keep it at 300~400℃ for 0.5~2h, and then calcin it at 450~650℃ for 2~5h.

Citation Information

Patent Citations

  • Carbon catalyst for decomposition of hazardous substance, hazardous-substance-decomposing material, and method for decomposition of hazardous substance

    CA2781989A1

  • Surface modified aluminum oxide adsorbent and preparation method thereof

    CN120054412A